Six Flavors of Open Access: Successes and Possibilities for STM Journals - Okerson, Ann (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
A broad commitment among participants in the scientific and scholarly publishing community to achieving the widest possible access to the literature has begun to bear fruit. Many of the players have had this kind of commitment all along, for example, through sharing around of preprints in physical sciences disciplines. As everyone knows, Paul Ginsparg's e-print server, arXiv, started in 1991, when he automated the high energy physics community's pre-electronic article-sharing practices, creating a mechanism for these articles to be submitted and mounted on a server. In turn, this innovation led the way for other disciplines; it is estimated today that perhaps 140 e-print servers from small to large-scale exist.